2016
DOI: 10.1039/c6ra06301b
|View full text |Cite
|
Sign up to set email alerts
|

A photoswitchable diarylethene heterodimer for use as a multifunctional logic gate

Abstract: A photoswitchable diarylethene heterodimer was prepared and its applications to logic gates were successfully demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Remarkably, Andréasson, Pischel, and Gust have shown that all‐photonic molecular logic devices can also perform various other logic operations, in addition to password authorization . The photonic reset function of photochromic security devices is also superior to that of other chemical logic systems with reset capability, in which the accumulation of chemical waste and dilution restrict the number of times the system can be recycled.…”
Section: Molecular Logic Gate‐based User Authorization Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, Andréasson, Pischel, and Gust have shown that all‐photonic molecular logic devices can also perform various other logic operations, in addition to password authorization . The photonic reset function of photochromic security devices is also superior to that of other chemical logic systems with reset capability, in which the accumulation of chemical waste and dilution restrict the number of times the system can be recycled.…”
Section: Molecular Logic Gate‐based User Authorization Systemsmentioning
confidence: 99%
“…The latter are macroscopic analytical devices that, similar to the way the olfactory system operates, can interact non‐specifically with a wide range of analytes and discriminate among them by creating a wide range of unique identification patterns . Hence, the main difference between 8 and the molecular keypad locks discussed before is that instead of generating a single digital output (0 or 1) for each code entry, it associates each password with a unique emission “signature” that enables it to authorize multiple users.…”
Section: User Authorization By Pattern‐generating Fluorescent Molecumentioning
confidence: 99%
“…Since then, various types of fluorescent diarylethenes with disulfonylbenzothiophene groups have been published (Scheme 1). [21][22][23] In the course of this research, we were interested in disulfonyl derivative 2 and considered various ways to synthesize this material. [4][5][6]18,19 Diarylethene 1 is a photochromic material that can be readily produced through the Suzuki reaction using dibromothiophene as a starting material.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-photochromic systems can be used to perform logic gate or keypad lock functions. 6,7,[31][32][33][34][35][36][37] The basis of a keypad lock is that the correct inputs must be entered in the correct order to diarylethene unit. The inputs of UV light and red light needed to be applied in sequence in order to produce a fluorescent state.…”
Section: Introductionmentioning
confidence: 99%